High performance of Ni0.9Mn1.8Mg0.3O4 spinel nanoceramic microbeads via inkjet printing and two step sintering. Issue 41 (11th April 2016) - Chen, Long; Wang, Junhua; Huang, Cuiping; Zhang, Qinan; Chang, Shannan; Chang, Aimin; Yao, Jincheng
Abstract : The effect of two step sintering process on the microstructure and electrical properties of inkjet printing high performance Ni0.9 Mn1.8 Mg0.3 O4 ceramic microbead materials with lower thermal time constant and higher material constant is investigated. Abstract : We report a simple and effective in situ inkjet printing method for the fabrication of nanostructured and highly dense Ni0.9 Mn1.8 Mg0.3 O4 (NMM) spinel oxide nanoceramic microbeads materials. In our method, the ceramic inks are fabricated that single cubic spinel NMM nanocrystallines synthesized via co-precipitation method, disperse well in organic solution, and have shown perfect dispersibility and stability. After inkjet printing using these ceramic inks, NMM microbeads are sintered via two-step sintering (TSS) process at different temperatures. The sintering behavior, microstructure and electrical properties of NMM nanoceramic microbeads prepared via TSS process are investigated and characterized systematically. These results indicate that high performance of NMM microbeads with moderate resistance values (98 331–174 601 Ω), lower thermal time constant (58–147 ms), and higher material constant (4176–4309 K) are achieved by tuning the sintering temperatures.